Respuesta :
x^2 + 3x - 5 = 0
x^2 + 3x = 5
x^2 + 3x + 2.25 = 5 + 2.25
(x + 1.5)^2 = 7.25
x + 1.5 = (+-) sqrt 7.25
x = -1.5 (+-) 2.69
x = -1.5 + 2.69 = 1.19 <=== ur answer
x = -1.5 - 2.69 = -4.19 <=== ur answer
x^2 + 3x = 5
x^2 + 3x + 2.25 = 5 + 2.25
(x + 1.5)^2 = 7.25
x + 1.5 = (+-) sqrt 7.25
x = -1.5 (+-) 2.69
x = -1.5 + 2.69 = 1.19 <=== ur answer
x = -1.5 - 2.69 = -4.19 <=== ur answer
Answer:
1.19, –4.19 are correct option .
Step-by-step explanation:
Given : x² +3x -5 = 0.
To find : Solve the equation by completing the square. Round to the nearest hundredth .
Solution : We have given that
x² +3x -5 = 0.
On multiplying and divide by 2 to the term 3x .
x² + [tex]\frac{2}{2}[/tex] * 3x -5 = 0.
On adding and subtracting the square of [tex]\frac{3}{2}[/tex]
[tex]x^{2} + 2 * \frac{3x}{2} +(\frac{3}{2}) ^{2} - (\frac{3}{2} )^{2} - 5 = 0[/tex].
We can see first three terms are square
[tex](x+ \frac{3}{2} )^{2}[/tex] - [tex](\frac{3}{2}) ^{2}[/tex] -5 = 0
[tex](x+ \frac{3}{2} )^{2}[/tex] - [tex](\frac{9}{4})[/tex] -5 =0
On solving
[tex](x+ \frac{3}{2} )^{2}[/tex] - [tex](\frac{29}{4})[/tex] =0
On adding both sides by [tex](\frac{29}{4})[/tex]
[tex](x+\frac{3}{2} )^{2}[/tex] = [tex](\frac{29}{4})[/tex]
Taking square root
[tex](x+\frac{3}{2})[/tex] = ± [tex]\sqrt{\frac{29}{4} }[/tex].
[tex](x+\frac{3}{2})[/tex] = ± [tex]{\frac{5.38}{2} }[/tex].
[tex](x+\frac{3}{2})[/tex] = ± 2.69 (it has two sign , so we will solve for both)
For + 2.69
On subtracting [tex](\frac{3}{2})[/tex] both side.
[tex](x+\frac{3}{2})[/tex] = + 2.69
x = + 2.69 - [tex](\frac{3}{2})[/tex]
x = [tex](\frac{5.38 -3}{2})[/tex].
x = [tex](\frac{2.38}{2})[/tex].
x = 1.19
For - 2.69
On subtracting [tex](\frac{3}{2})[/tex] both side.
[tex](x+\frac{3}{2})[/tex] = - 2.69
x = - 2.69 - [tex](\frac{3}{2})[/tex]
x = [tex](\frac{-5.38 -3}{2})[/tex].
x = [tex](\frac{-8.38}{2})[/tex].
x = - 4.19.
Therefore, 1.19, –4.19 are correct option .